2008
DOI: 10.1093/molbev/msm255
|View full text |Cite
|
Sign up to set email alerts
|

Excavating Past Population Structures by Surname-Based Sampling: The Genetic Legacy of the Vikings in Northwest England

Abstract: The genetic structures of past human populations are obscured by recent migrations and expansions and have been observed only indirectly by inference from modern samples. However, the unique link between a heritable cultural marker, the patrilineal surname, and a genetic marker, the Y chromosome, provides a means to target sets of modern individuals that might resemble populations at the time of surname establishment. As a test case, we studied samples from the Wirral Peninsula and West Lancashire, in northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(46 citation statements)
references
References 30 publications
1
43
1
1
Order By: Relevance
“…Therefore, no indication for a historical admixture event during the Roman Period was observed in this Flemish study to clarify the observed high Y-chromosomal diversity within the communities. This is in contrast to a previous study of indigenous patrilines within Northwestern English communities using a similar surname-based sampling approach, where evidence was found for a historical geneflow event from Scandinavia to Northwest England during the Middle Ages (Bowden et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, no indication for a historical admixture event during the Roman Period was observed in this Flemish study to clarify the observed high Y-chromosomal diversity within the communities. This is in contrast to a previous study of indigenous patrilines within Northwestern English communities using a similar surname-based sampling approach, where evidence was found for a historical geneflow event from Scandinavia to Northwest England during the Middle Ages (Bowden et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…To deal with this problem, the unique link between a heritable cultural marker -the patrilineal surname-and a genetic marker-the Y chromosome -provides an opportunity to target sets of living individuals that might resemble populations at the time of surname establishment until today (Bowden et al, 2008;Larmuseau et al, 2012b). In addition, it is possible to organise sampling campaigns for a specific location by using the genetic genealogical approach, which selects indigenous surnames based on the historical documents and carries out in-depth genealogical research for each DNA donor to exclude descendants of illegitimate children, adoptees, extra-pair paternity (EPP) and migrants with an adopted local surname (Larmuseau et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies need to give insights into whether surname-selection may still give an extra possibility to provide an even older sample for the population genetic analysis as patrilineal surnames are already present in Western Europe earlier than the seventeenth century. 22,39 CONCLUSION By linking a huge number of Y-chr sub-haplogroups to a certain location at a specific time period, it became possible to study the effects of past migrations on the micro-geographic population genetic pattern within the Western-European region of Brabant. Significant genetic differentiation was observed in the oldest studied time periods (1675-1700).…”
Section: Temporal Differentiation On Y-chromosomal Gradient Mhd Larmumentioning
confidence: 99%
“…Several studies over the past few years [1][2][3][4][5][6] have investigated the relationship between surnames and Y chromosomes, and have generally concluded that surnames are informative markers that can help disentangle hidden population structure and give insight into past historical events.…”
Section: Introductionmentioning
confidence: 99%